Pertanggungjawaban Pidana dan Pembuktian Terbalik Dalam Tindak Pidana Korupsi dan Pencucian Uang oleh Pegawai Direktorat Jenderal Pajak (Studi Kasus Rafael Alun Trisambodo) - Nathan Thomas (Journal of Citizenship, 2025)
This study aims to analyze criminal liability and the implementation of the reverse burden of proo in corruption and money laundering cases involving Rafael Alun Trisambodo, an employee of the Directorate General of Taxes. Article 4 paragraph (8) of Government Regulation Number 53 of 2010 on Civil Servant Discipline explicitly prohibits civil servants, including those within the Dorectorate General of taxes, from receiving any form of gift related to the performance of their duties or authority. The research employs a normative juridical method using a case approach and a regulatory approach to examine the legal issues involved. The findings indicate that the elements of criminal liability in the corruption and money laundering offenses are fulfilled through the existence of unlawful conduct, intent, the capacity for responsibility, and the absence of justifying or exexcusing grounds. The establishment of familiy owned companies, concealment of financial flows, and disproportionate asset growth demonstrate a deliberate effort to obtain and disguise illicit proceeds. Decisions of the Corruption Court and the Supreme Court further show that the reverse burden of proof operates effectively, requiring the defendant to prove the lawful origin of his assests once the prosecutor presents sufficient initial evidence. The defendant’s inability to provide a legally valid explanation reinforced the imposition of criminal sanctions. Overall, this study highlights the significance of the reverse burden of proof and the principles of criminal liability as essential tools in combating corruption and money laundering, particularly in cases involving the abuse of authority by public officials.